Comparative evaluation of Quality of Life indicators: towards developing a comprehensive standard model for measuring Quality of Life - JALAL ABU-ALROP (European Journal of Government and Economics)
This study aims to improve the understanding of quality of life (QoL) by evaluating key indicators, identifying influential factors, and assessing their relative weights. This study utilizes panel data from 181 cases across 32 European countries (2012-2017). The study employs exploratory and confirmatory factor analyses to create a comprehensive QoL measurement model. Four primary factors were found to influence QoL in Europe: economy, health, education, and governance quality. The study compares five common QoL indicators—income, GDP, life expectancy, the Human Development Index (HDI), and the Legatum Prosperity Index—against this model. Results show that the HDI is the most balanced indicator, while others exhibit biases. The study emphasizes the need for more precise and comprehensive QoL measures and recommends applying exploratory and confirmatory factor analyses to enhance them. Future research should validate the model in other regions and further improve QoL measurement.